TNFα inhibitors reduce bone loss in rheumatoid arthritis independent of clinical response by reducing osteoclast precursors and IL-20. (27th September 2020) - Al-Bogami, Mohammed; Bystrom, Jonas; Clanchy, Felix; Taher, Taher E; Mangat, Pamela; Williams, Richard O; Jawad, Ali S; Mageed, Rizgar A
Abstract: Objectives: About half of RA patients treated with TNFα inhibitors either do not respond or lose their initial therapeutic response over time. The clinical response is measured by reduction in DAS28, which primarily reflects inflammation. However, other effects of TNFα inhibitors, such as impact on bone erosion, are not assessed by DAS28. We aimed to examine the effect of TNFα inhibitors on bone density, bone biomarkers and cytokine production in responder and non-responder patients and assessed mechanisms of action. Methods: BMD in the lumbar spine and femur neck of 117 RA patients was measured by DEXA scan. Bone turnover biomarkers CTX, osteoprotegerin (OPG), osteocalcin and RANKL were measured by ELISA. Levels of 16 cytokines in plasma and in tissue culture supernatants of ex vivo T cells were measured by multiplex assays and ELISA. The effect of treatment with TNFα inhibitors on blood mononuclear cell (MNC) differentiation to osteoclast precursors (OCP) was measured flow cytometry and microscopy. Results: TNFα inhibitors improved lumbar spine BMD but had modest effects on blood bone biomarkers, irrespective of patients' clinical response. Blood OCP numbers and the ability of monocytes to differentiate to OCP in vitro declined after treatment. Treatment also reduced RANK expression and IL-20 production. BMD improvement correlated with reduced levels of IL-20 in responder patients. Conclusion: This study reveals that TNFα inhibitors reduce lumbar spine bone loss in RA patients irrespective of changes in DAS28. The reduction in bone loss is associated with reduction in IL-20 levels in responder patients.